Workplace-based assessment of communication skills: A pilot project addressing feasibility, acceptance and reliability - Weyers, Simone; Jemi, Iman; Karger, André; Raski, Bianca; Rotthoff, Thomas; Pentzek, Michael; Mortsiefer, Achim (GMS Journal for Medical Education, 2016)
Background: Imparting communication skills has been given great importance in medical curricula. In addition to standardized assessments, students should communicate with real patients in actual clinical situations during workplace-based assessments and receive structured feedback on their performance. The aim of this project was to pilot a formative testing method for workplace-based assessment. Our investigation centered in particular on whether or not physicians view the method as feasible and how high acceptance is among students. In addition, we assessed the reliability of the method.Method: As part of the project, 16 students held two consultations each with chronically ill patients at the medical practice where they were completing GP training. These consultations were video-recorded. The trained mentoring physician rated the student’s performance and provided feedback immediately following the consultations using the Berlin Global Rating scale (BGR). Two impartial, trained raters also evaluated the videos using BGR. For qualitative and quantitative analysis, information on how physicians and students viewed feasibility and their levels of acceptance was collected in written form in a partially standardized manner. To test for reliability, the test-retest reliability was calculated for both of the overall evaluations given by each rater. The inter-rater reliability was determined for the three evaluations of each individual consultation.Results: The formative assessment method was rated positively by both physicians and students. It is relatively easy to integrate into daily routines. Its significant value lies in the personal, structured and recurring feedback. The two overall scores for each patient consultation given by the two impartial raters correlate moderately. The degree of uniformity among the three raters in respect to the individual consultations is low.Discussion: Within the scope of this pilot project, only a small sample of physicians and students could be surveyed to a limited extent. There are indications that the assessment can be improved by integrating more information on medical context and student self-assessments. Despite the current limitations regarding test criteria, it is clear that workplace-based assessment of communication skills in the clinical setting is a valuable addition to the communication curricula of medical schools.